Key Factors in the establishment of an academia-government center of public sector administrative data and policy research - Ayles, James; McDonald, Ted (International Journal of Population Data Science, 2018)
A collaborative between the Government of New Brunswick (GNB) and the University of New Brunswick to establish a center of public sector administrative data and policy research was envisioned in 2012. Subsequent work between the parties led to the establishment of the New Brunswick Institute for Research, Data and Training (NB-IRDT) in 2014. Academia-government partnerships are not unique in Canada, however what sets this apart is: 1) the legislative approach used to support research, 2) scope of administrative data made available, 3) value placed on anonymized linked data, 4) governance overseeing the partnership, and 5) measures taken to ensure the protection of citizens’ data. In 2017, the New Brunswick Act Respecting Research received proclamation. This Act serves to provide clarity and addresses gaps in access and use of personal / health data for research. The Act has opened the doors for NB-IRDT with data owners of public sector organizations. NB-IRDT may now receive pseudonymous personal data from any public sector program collecting personal information. The partnership is governed by several advisory committees each serving a different role in overseeing the growth of NB-IRDT; overall direction setting being led by a panel of Deputy Ministers and the Clerk (the senior ranking civil servant in GNB.) The collaboration is well positioned to support public policy research and fosters the use of evidence-based information in the development of government programs and services. The partnership has also helped to encourage new and innovative thinking within GNB about the value of linkable data to support decision-making.